THE IMPLEMENTATION OF COURSES AT THE MATHLAUL ANWAR UNIVERSITY IN THE CHARACTER FORMING OF PANCASILAIS STUDENTS - Tatu Munawaroh (Jurnal Visi Ilmu Pendidikan, 2023)
This study discusses Education and learning activities are the basis of human existence, so humans cannot be separated from teaching and learning activities. This study aims to determine Pancasila character education in teaching materials to shape students' civic character. The research design uses a qualitative approach and the method used is a case study. Data collection techniques using observation, interviews, and documentation. Testing the validity of the data with the extension of observation and triangulation. Processing and analysis of technical data using data reduction, data presentation, and verification. The results show that Pancasila values are integrated in the teaching materials of students and form the character of citizens who are religious, humanitarian, national unity, populist and deliberative or democracy, and social justice. Keywords: Character Education, Pancasila, Citizenship.